Influence of Natural Gas Production Chemicals on Scale Production in MEG Regeneration Systems - Yong, A.; Obanijesu, Emmanuel (Pergamon, 2015)
Monoethylene glycol (MEG), a common hydrate inhibitor in natural gas transportation pipelines is usually regenerated and reused to minimize operating costs. In this study, three corrosion inhibitors and a scale inhibitor were investigated to understand how production chemicals contribute to scaling (salt loading) at pretreatment and reclamation sections of the regeneration process. The first set of study involved the use of ScaleSoftPitzer software to investigate the possibility of salt deposition at the pretreatment stage. Experiments were then conducted at pretreatment stage for inhibitor doses of 250 ppm and 1000 ppm. The same sets of experiments were repeated by adding equal concentration of scale inhibitor with each corrosion inhibitor. In the second part of the study, rich MEG recovered from the pretreatment stage was regenerated by reconcentration and vacuum distillation techniques. The solids formed in the liquor were filtered, dried and weighed and the experiments performed at the pretreatment stage repeated. The results showed that level of scaling in the pretreatment stage was well predicted by the software. The experimental results were also consistent with the software predictions. Corrosion inhibitors produced salts that add up to the scaling problems while the scale inhibitor showed more adverse scaling effects comparatively.This is attributed to reduced hydration ability of scale inhibitors compared to corrosion inhibitors that contained smaller functional groups and large alkyl groups. Benzyl dimethyl hexadecylammonium chloride (B.D.H.C) showed higher scale formation ability compared to the other two corrosion inhibitors due to its polarity that influences its affinity for water. Alkalinity was another factor affecting scale formation; the higher the alkalinity, the higher the scale formation. Furthermore, the reclamation stage was found to be highly prone to corrosion and other impacts due to high total dissolved solids (TDS). Besides, a combination of corrosion and scale inhibitors in MEG regeneration system resulted in higher scaling effects compared to the effect of individual inhibitor due to the synergistic interaction between the two inhibitors. The findings of this study show significant implications in large scale continuous operation where salts dissolved in MEG could precipitate to cause scaling, corrosion and gunking amongst others. Escaping less soluble divalent ions are also capable of salting out downstream to cause the same problems within the pipeline and refinery. All these will adversely influence the process safety and the environment.